2014
DOI: 10.1093/annonc/mdu363
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, placebo-controlled trial of weekly paclitaxel and saracatinib (AZD0530) in platinum-resistant ovarian, fallopian tube or primary peritoneal cancer

Abstract: Clinicaltrials.gov NCT01196741; ISRCTN 32163062.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
60
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 22 publications
10
60
0
1
Order By: Relevance
“…A phase II trial in 37 patients with previously-treated advanced nonsmall-cell lung cancer, however, showed some signal of benefit, with 2 of 31 evaluable patients having partial responses lasting 3.7 and 14.6 months, and 6 patients being progression free at 16 weeks (primary endpoint) [28]. Saracatinib has not been studied in combination with other therapeutic agents in colorectal cancer but has not improved outcomes in combination studies with gemcitabine in pancreatic cancer [29] or with paclitaxel in platinum-resistant ovarian, fallopian and primary peritoneal cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…A phase II trial in 37 patients with previously-treated advanced nonsmall-cell lung cancer, however, showed some signal of benefit, with 2 of 31 evaluable patients having partial responses lasting 3.7 and 14.6 months, and 6 patients being progression free at 16 weeks (primary endpoint) [28]. Saracatinib has not been studied in combination with other therapeutic agents in colorectal cancer but has not improved outcomes in combination studies with gemcitabine in pancreatic cancer [29] or with paclitaxel in platinum-resistant ovarian, fallopian and primary peritoneal cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous human ovarian adenocarcinoma cells (HOAC) are sensitive to Dasatinib, an inhibitor of c-Src, which synergizes with carboplatin and paclitaxel in a cell-specific manner [8, 9]. A phase II clinical trial in platinum-resistant ovarian cancer patients showed no advantage in the association of Saracatinib, a dual inhibitor of Src and Abl, with paclitaxel [22]. Dasatinib, which entered in phase I in ovarian cancer patients, could however show more promising results because of its action on Src, Bcl-Abl, c-kit, PDGFβ and other kinases [23].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of AZD0424 has not been previously described and this compound is currently partnered with Cancer Research UK -the sponsor of the ongoing clinical trials. c-Src as a target in oncology was initially pursued by AstraZeneca as an anti-invasive target but failed to deliver robust efficacy in clinical trials, including in gastric [24], castration-resistant prostate [25], hormone-receptornegative metastatic breast [26] and platinum-resistant ovarian [27] cancers. It is interesting to note that other Src inhibitors developed contemporaneously with saracatinib, such as dasatinib (Bristol Myers Squibb) and bosutinib (Pfizer) were ultimately approved for the treatment of chronic myeloid leukaemia (CML) on the basis of their potent activity against Bcr-Abl kinase rather than their Src activity.…”
Section: Inhibitors Of Src and Abl Kinases: Discovery Of Saracatinib mentioning
confidence: 99%